The Effectiveness of Using Interactive Animation Media in Enhancing Interest in Science Learning in Primary Schools: Systematic Literature Review - Salma Khairunnisa; Rohmani Rohmani (Institute of Multidisciplinary Research and Community Service, 2026)
Science learning in elementary schools is still dominated by conventional teacher-centered methods, which often result in low student motivation, boredom, and limited active participation in the learning process. However, science is a subject that contains many abstract concepts and therefore requires more engaging, interactive, and student-friendly learning media to support better understanding. This study aims to analyze the effectiveness of interactive animation media in improving students’ interest in learning science at the elementary school level based on previous research. The method used is a Systematic Literature Review (SLR) guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Data were collected through literature searches in the Google Scholar and SINTA databases covering publications from 2021 to 2025. The search was conducted using the keywords “interactive animation media,” “learning interest,” “science learning,” and “elementary school.” The selected articles were then screened based on inclusion and exclusion criteria, resulting in 10 relevant studies for further analysis. The findings show that interactive animation media effectively increase students’ attention, interest, participation, and enthusiasm in science learning. In addition, this media helps visualize abstract concepts in more concrete forms, making them easier for elementary school students to understand. The implications of this study indicate that interactive animation media can be used as an effective alternative learning tool to improve the quality of science learning; therefore, teachers should integrate it in a well-planned manner supported by adequate facilities and teacher training to ensure optimal implementation in the classroom. In conclusion, interactive animation media plays an important role in creating more effective, interactive, and enjoyable science learning in elementary schools. Keywords: interactive animation media, learning interest, science education, primary school.